Supplier dependence and R&D intensity: The moderating role of network centrality and interconnectedness - Kim, Dong‐Young; Zhu, Pengcheng (Journal of Operations Management, 2018)
This study examines whether financial dependence upon a few customers is negatively related to the allocation of innovation resources of supplier firms. Furthermore, this study investigates whether these negative effects of supplier dependence on research and development (R&D) intensity are reduced when the supplier leverages social capital conceptualized in terms of eigenvector centrality and interconnectedness. Using panel data, we find that a supplier firm's dependence upon major customers has a negative relationship with the supplier firm's R&D intensity. Our results, however, reveal that a dependent supplier having high eigenvector centrality or working with other companies that are densely connected to each other mitigates the negative effects of supplier dependence on R&D intensity. These findings highlight the importance of external information or resources being available in supply networks when suppliers that are dependent upon major customers explore and exploit opportunities for new product development.